Millennial-Scale Interaction between Ice Sheets and Ocean Circulation during Marine Isotope Stage 100 - Ohno, Masao; Hayashi, Tatsuya; Sato, Masahiko; Kuwahara, Yoshihiro; Mizuta, Asami; Kita, Itsuro; Sato, Tokiyuki; Kano, Akihiro (Frontiers in Earth Science, 2016)
Waxing/waning of the ice sheets and the associated change in thermohaline circulation have played an important role in global climate change since major continental ice sheets appeared in the northern hemisphere about 2.75 million years ago. In the earliest glacial stages, however, establishment of the linkage between ice sheet development and ocean circulation remains largely unclear. Here, we show new high-resolution records of marine isotope stage 100 recovered from deep-sea sediments on the Gardar Drift, in the subpolar North Atlantic. Results of a wide range of analyses clearly reveal the influence of millennial-scale variability in iceberg discharge on ocean surface condition and bottom current variability in the subpolar North Atlantic during marine isotope stage 100. We identified eight events of ice-rafted debris, which occurred mostly with decreases in sea surface temperature and in current components indicating North Atlantic Deep Water. These decreases are interpreted by weakened deep water formation linked to iceberg discharge, similarly to observations from the last glacial period. Dolomite fraction of the ice-rafted events in early MIS 100 like the last glacial Heinrich events suggests massive collapse of the Laurentide ice sheet in North America. At the same time, our early glacial data suggest differences from the last glacial period: absence of 1470-year periodicity in the interactions between ice sheets and ocean, and northerly shift of the ice-rafted debris belt. Our high-resolution data largely improve the picture of ice-sheet/ocean interactions on millennial time scales in the early glacial period after major Northern Hemisphere glaciation.